Adjuvant radiotherapy and chemotherapy in early-stage diffuse large B cell lymphoma of head and neck with extranodal involvement. Issue 1 (1st January 2019) - Peng, Cuiying; Ho, Joshua; Bai, Harrison X.; Huang, Yuqian; Huang, Raymond Y.; Yang, Li
ABSTRACT: Objectives: Diffuse large B cell lymphoma (DLBCL) is a heterogeneous lymphoma with a variety of presentations and treatment modalities. With the introduction of immunotherapy as an addition to chemotherapy (CT), there is ongoing debate about the role of radiotherapy (RT) in treatment and a need to clarify differences by specific anatomic locations. Methods: We identified a cohort of 1929 individuals with limited stage (stage I and II) head and neck DLBCL with extranodal involvement from the National Cancer Data Base. Overall survival (OS) was evaluated by Kaplan-Meier analysis, multivariable Cox proportional hazard regression, and propensity score-matched analysis. Results: Multi-agent CT plus RT was associated with longer OS (HR, 0.763; 95% CI, 0.614 to 0.948; p  = 0.015) when compared with multi-agent CT alone on multivariate analysis. After propensity score matching to account for confounding variables, multi-agent CT plus RT was associated with longer OS than those who received multi-agent CT alone (HR = 0.769; 95% CI, 0.609–0.971; p  = 0.027). The survival benefit persisted in patients over the age of 60 years and those who received RT within 180 days of CT. However, there was no significant difference in OS between the two groups in subgroup analysis of patients who received immunotherapy. Conclusion: The addition of RT to CT resulted in longer OS in patients with limited stage head and neck DLBCL with extranodal involvement.